The Effectiveness of "Segi Busui" Booklet Media toward Knowledge and Attitude concerning Balanced Nutrition in Breastfeeding Mothers of 0-6 Months - Darmayanti, Mey Linda; Yuniastuti, Ari; Budiono, Irwan (Journal of Maternal and Child Health, 2023)
Background: Balanced nutrition for mothers during breastfeeding is closely related to breast milk production, puerperal recovery, and other influences on the sustainability of the puerperal or breastfeeding mother. The thing that needs to concern is that if the nutrition for breastfeeding mothers is not met, the nutritional needs for breast milk production will be taken from the mothers’ body reserves. This condition will cause the mother to experience the risk of disease and chronic malnutrition. This study aims to develop the "Segi Busui" Booklet media and to determine the effectiveness of the "Segi Busui" booklet media toward knowledge and attitude concerning balanced nutrition in breastfeeding mothers of 0-6 months babies. Subjects and Method: The method used in the study was Research and Development (RnD) using the Borg and Gall model. The type of study used to determine the effectiveness was pre-experimental with one group pretest-posttest design. The sample in this study was 48 breastfeeding mothers of 0-6 months babies. The dependent variables were knowledge and attitudes. The independent variable was the booklet “Segi Busui". The data were collected using questionnaires. The analysis technique used was the Wilcoxon test. Results: The average score of maternal knowledge increased after (Mean= 19.65; SD= 0.93) the "Segi Busui" booklet intervention compared to before the intervention (Mean= 13.06; SD= 1.74), and the result was statistically significant (p<0.001). Meanwhile, the maternal attitude score increased after (Mean= 66.71; SD= 3.48) the "Segi Busui" booklet intervention compared to before the intervention (Mean= 53.60; SD= 5.93), and the result was statistically significant (p<0.001) Conclusion: The “Segi Busui" booklet media is effective in increasing knowledge and attitudes concerning balanced nutrition in breastfeeding mothers of 0-6 months babies. Keywords: booklet media, knowledge, attitude, balanced nutrition of breastfeeding mothers. Correspondence: Mey Linda Darmayanti. Master’s Program in Public Health, Universitas Negeri Semarang. Jl. Kelud Utara III No.15, Semarang, Central Java 50237. Email: meylindadarmayanti1605@gmail.com. Mobile 085641131716.